2012
DOI: 10.1039/c2cc00025c
|View full text |Cite
|
Sign up to set email alerts
|

A phosphonated triarylmethyl radical as a probe for measurement of pH by EPR

Abstract: A new water soluble phosphonated tetrathiatriarylmethyl radical has been synthesized and its application for pH measurement in a physiological range by EPR is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 13 publications
0
54
0
Order By: Relevance
“…TAMs have advantages over nitroxides in extraordinary stability toward tissue redox processes, longer relaxation time and narrower line width making them particularly attractive for imaging applications. Applications of TAM radicals as functional probes include EPR oximetry (ArdenkjaerLarsen et al, 1998;Golman et al, 2000;Krishna et al, 2002) and recently reported sensitivity to the superoxide anion Kutala et al, 2008) and pH (Bobko et al, 2007a;Dhimitruka et al, 2008;Driesschaert et al, 2012). On the other hand NRs have tremendous advantage over TAMs in well-developed chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…TAMs have advantages over nitroxides in extraordinary stability toward tissue redox processes, longer relaxation time and narrower line width making them particularly attractive for imaging applications. Applications of TAM radicals as functional probes include EPR oximetry (ArdenkjaerLarsen et al, 1998;Golman et al, 2000;Krishna et al, 2002) and recently reported sensitivity to the superoxide anion Kutala et al, 2008) and pH (Bobko et al, 2007a;Dhimitruka et al, 2008;Driesschaert et al, 2012). On the other hand NRs have tremendous advantage over TAMs in well-developed chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Trityl radicals have not only been employed in EPR oximetry, 14,27,28 but also in many other applications, e.g., specific detection of superoxide radical anions, [29][30][31] pH measurements, 32,33 as well as analysis of redox status. 34 Trityl-based spin labels were used for distance measurements, e.g., in nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent triarylmethyl radicals [1] (trityls, TAMs, see Figure 1) have recently been proposed as ideal spin probes for numerous applications in biology, [25] analytical chemistry, [6] and materials science. [7] Trityls are stable towards the majority of biological oxidants and reductants.…”
Section: Introductionmentioning
confidence: 99%